Effect of abiotic weather on twig damage in amla (Emblica officinalis) by Betousa stylophora - PATEL, M G; PATEL, G P; SHEKH, A M; PATEL, J R; PATEL, H R; PATEL, M J (The Indian Journal of Agricultural Sciences, 2013)
The infestation of gall forming black caterpillar, Betousa stylophora Swinhoe and ’Gujarat 1’ amla (Emblica officinalis Gaertn.) in middle Gujarat agro-climate was found during 4th week of June to 3rd week of January during 1994-95. The siginificant negative association has been observed between B. stylophora and rainfall, wind velocity, minimum temperature, morning and.evening vapour pressure, morning and evening relative humidity, whereas bright sunshine hours, evening vapour pressure deficit and temperature humidity ratio showed significant positive correlation. During 1995-96 its activity started from 4th week of July and continued till 3rd week of January. The siginificant negative association of B. stylophora was observed with evaporation, wind velocity, maximum temperature, minimum temperature, morning and evening vapour pressure and morning vapour pressure deficit. The path analysis showed that amongst the weather variable morning time vapour pressure had direct significant effect on pest activity. These findings can be utilized in forecasting and preventing the damage of B. stylophora on amla by taking recommended plant protection measures.